Improving The Quality of Surgical Operations in The Ambulatory Polyclinic Service - Ergashev Ulugbek Yusufjanovich; Mominov Alisher Tashkarganovich; Minavarkhojayev Ravshankhuja Rakhmatkhuja ogli; Ernazarov Khojimurod Irsaliyevich (Scientific Trends, 2023)
The protection of public health is one of the urgent and most significant problems not only of health care, but also of the state as a whole. Negative changes in the social and economic spheres of society, high rates of morbidity and mortality of the population lead to a deterioration in public health and numerous problems in healthcare system, which increases the population's need for medical care (4, 7, 12,17). Outpatient care is the most widespread and accessible type of medical care; it is received by about 80% of all patients who apply to healthcare organizations (5, 8, 10, 13). The availability of outpatient care is provided by a wide network of institutions. In 2012, more than 1,100 outpatient clinics operated, providing medical care to more than 10 million people. The problem of improving outpatient care for the population is a priority, strategic direction of healthcare reform at the present stage. It is outpatient care that should be a mass public form of providing medical care to the population.
Keywords: optimization, organization, surgical care, population, employees, lifestyle, social status.